2021
DOI: 10.1186/s13018-021-02204-z
|View full text |Cite
|
Sign up to set email alerts
|

High expression of ABCG2 is associated with chemotherapy resistance of osteosarcoma

Abstract: Objectives Previous studies showed overexpression of ABCG2 in a variety of tumor tissues, which could potentially indicate the probability of chemotherapy resistance. This study aimed to reveal the role of ABCG2 in the development of chemotherapy resistance and the prognosis of osteosarcoma (OS). Methods Sixty-eight OS patients were included in this study. Tumor tissues were collected for each patient during surgery. DOX-resistant OS cell lines wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…Our group and others have found that the ABCG2 transporter is highly expressed in the spheres from PCa which correlates with a level of high drug resistance of this CSCs population [ 32 , 104 ]. In several other studies, the CSCs have showed to have a level of high resistance to multiple drugs including taxanes, tyrosine kinase and topoisomerase inhibitors, among others [ 4 , 105 , 106 , 107 ]. ALDH1, which is another stemness marker, has been implicated in changes in the metabolism of chemotherapeutic agents, reducing radio-sensitivity in the PCa cell lines [ 105 ].…”
Section: Cancer Stems Cells and Epithelial–mesenchymal Transition In ...mentioning
confidence: 99%
“…Our group and others have found that the ABCG2 transporter is highly expressed in the spheres from PCa which correlates with a level of high drug resistance of this CSCs population [ 32 , 104 ]. In several other studies, the CSCs have showed to have a level of high resistance to multiple drugs including taxanes, tyrosine kinase and topoisomerase inhibitors, among others [ 4 , 105 , 106 , 107 ]. ALDH1, which is another stemness marker, has been implicated in changes in the metabolism of chemotherapeutic agents, reducing radio-sensitivity in the PCa cell lines [ 105 ].…”
Section: Cancer Stems Cells and Epithelial–mesenchymal Transition In ...mentioning
confidence: 99%
“…The search strategy employed in this review identified 18 clinical studies published between 1995-2021 that assessed expression of one gene [74], 12 proteins [26,28,36,48,[75][76][77][78][79][80][81][82][83] and ten ncRNAs [82,[84][85][86][87] in relation to relapse, metastasis and response to MAP therapy in OS patients (Table 4). Eight of these proteins overlapped with factors investigated in cell models of chemoresistance.…”
Section: Patient Demographicmentioning
confidence: 99%
“…Seven studies investigated more than one patient outcome measure, two studies used both biopsy and surgical samples and one study used biopsy and relapsed samples. Response was used as a patient outcome measure in 17 studies and all were defined by the standard percentage necrosis threshold [26,28,36,48,[74][75][76][77][78][79][80][81][82][84][85][86][87]. Relapse as a patient outcome measure was variably defined with 1/7 studies using local relapse only [81], 2/7 studies including relapse at any site [77,79] and the remaining studies providing no clear definition [36,76,80,83].…”
Section: Patient Demographicmentioning
confidence: 99%
See 1 more Smart Citation
“…However, several studies have investigated the regulatory mechanism underlying ABCG2 expression in OS [ 79 , 80 ]. An association was found between high ABCG2 expression in patients with OS and poor survival and response to chemotherapy [ 81 ]. The role of ABCG2 in OS prediction was also established [ 80 ].…”
Section: Mdr Genes and Membrane Carriersmentioning
confidence: 99%